Milled rapeseeds and oats decrease milk saturated fatty acids and ruminal methane emissions in dairy cows without changes in product sensory quality - Halmemies-Beauchet-Filleau, Anni; Jaakkola, Seija; Kokkonen, Tuomo; Turpeinen, Anu M.; Givens, D. Ian; Vanhatalo, Aila (Frontiers in Animal Science, 2023)
Plant lipids in the diet are known to modify milk fatty acid (FA) composition and mitigate ruminal methane emissions. The objective of the present work was to examine the potential of milled rapeseeds and oats to decrease both milk saturated FAs and ruminal methane emissions in practical farm settings. In the pilot study, six Finnish Ayrshire cows were fed a control diet for 3 weeks, which was then followed by a lipid-rich test diet for 3 weeks. The experimental diets were based on grass silage supplemented with barley and rapeseed meals in the control diet and with oats and milled rapeseeds in the test diet. The lipid inclusion rate was 55 g/kg dry matter (DM). In the main study, the whole Finnish Ayrshire research herd in milk (n = 49–59) was used in a switch-back-designed study. The cows were fed a control diet for 3 weeks, then a test diet for 4 weeks, and, finally, a control diet for 3 weeks. The diets were the same as in the pilot study except for a lower lipid inclusion level of 50 g/kg DM. The test diet decreased DM intake by 15% and energy-corrected milk (ECM) yield by 13% in the pilot study. The adjustment of supplemental lipids from 55 g/kg to 50 g/kg DM was successful, as the DM intake decreased only by 4% relative to the control diet in the main study. Furthermore, the yields of milk, lactose, protein, and fat were also unaffected by dietary lipids in the main study. The milk fat composition was significantly altered in both studies. The milk fat saturated FAs were decreased by 16%–20% in the test diet, mainly due to the de novo FAs of 6- to 16-carbons (a reduction of 22%–48%). Milk fat cis-9 18:1 was increased by 63%–78% in the test diet relative to the control. Dairy products’ (milk, butter, and cheese) organoleptic quality was not compromised by the modified lipid profile. Ruminal methane and hydrogen intensities (n = 23; g or mg/kg ECM) were 20% and 39% lower, respectively, in the test diet than in the control diet. This reduction can be attributed to a lower amount of organic matter fermented in the rumen, as indicated by the lower DM intake and nutrient digestibility.